Belonging to The Homeland in The Noble Quran: الانتماء للوطن في ضوء القرآن الكريم - al-Mansoori, Salem Ahmed; Abdul Hamid, Ahmad Faisal (Al-Muqaddimah: Online Journal of Islamic History and Civilization, 2021)
The Book of the Almighty Allah, the great Quran is considered as a constitution and way of life for humans as it includes interests of people in their religious and worldly affairs. The Quran talks about the residence of man, his homeland, his feeling and inclination towards that homeland and this what is called-belonging (to the homeland). Allah created man with a disposition to love his homeland and incline to it. All men of different ages, races and genders love their homes and the Shariah does not oppose or reject this tendency, feeling and love of the homeland. The researcher depended on the inductive method through collecting texts that study verses related to belongingness to the homeland in light of the Noble Quran. He also used the analytical method to analyze the collected information. The research found the following results. The common sense of humans in term of association of a person with his homeland and inclination to it accords with the Shariah as deduced from the Book of the Almighty Allah and the meaning of its verses which explain legality of association with the homeland. Commitment, adherence to and implementation of values of association with the homeland cornubite greatly to supporting and strengthening the homeland if it is taken and implemented with sincerity and honesty and considered as an act of worship (of Allah). Moreover, several verses of the Quran indicated that the homeland is favour as it includes the residence of man, his livelihood and what Allah put on it from bounties and blessings. Additionally, the Almighty Allah explained in the Quran that the man is inclined to love his homeland, incline towards and defend it. The Almighty Allah also showed the great effect on the souls of people when they leave their homelands and families whether for seeking livelihood, as punishment or for saving their religion for the sake of Allah and His pleasure.